Relationship of age at menarche on anthropometric index and menstrual irregularity in late adolescent girls in Seoul - Seung Eun Lee; Joo Yun Yang; Ji Hyun Lee; Han Wool Kim; Hae Soon Kim; Hye Jin Lee; Ji Young Oh; Yeon Ah Sung (Korean Society of Pediatric Endocrinology, 2013)
PurposeTo examine the relationship between menarcheal age and anthropometric indices and menstrual irregularity in late adolescent girls in Seoul.MethodsWe surveyed 4,218 fertile adolescent girls between the ages of 16 and 18 years to determine their anthropometric indices and menarcheal age. Measurements were taken from June 2008 to October 2009 at seven girl's high schools in Seoul, Korea. Participants were offered self-report questionnaire as a survey tool that included questions on anthropometric indices (height, weight, waist circumference), menarcheal age, menstrual pattern, frequency of menstruation per year.ResultsThe participants were categorized into three groups based on menarcheal age: early menarche group (younger than 2 standard deviations [SD]), mid menarche group (within ±2 SD), late menarche group (older than 2 SD). The mean age of early menarche group was 9.9±0.2 years, mid menarche group 12.5±0.9 years, late menarche group 15.1±0.3 years (P < 0.001). Heights were recorded as 160.4±5.2 cm, 161.8±4.9 cm, 162.3±4.7 cm in early, mid, and late menarche group, respectively (P = 0.001). Body mass index (BMI) and waist circumference significantly were lager in early menarche group than mid and late menarche ones (P < 0.001). The menarcheal age had a positive correlation with height and negative correlations with weight, BMI, waist circumference (P < 0.001). The prevalence of oligomenorrhea was more frequent in late menarche group than early and mid menarche group.ConclusionThe menarcheal age have positive relationship with height and inverse relationship with BMI and waist circumference in late adolescent girls in Seoul. Late menarcheal girls are disposed to have menstrual irregularity compared to early menarcheal girls.